Avoiding short circuits from zinc metal dendrites in anode by backside-plating configuration - Higashi, Shougo (2018)
Portable power sources and grid-scale storage both require batteries combining high energy density and low cost. Zinc metal battery systems are attractive due to the low cost of zinc and its high charge-storage capacity. However, under repeated plating and stripping, zinc metal anodes undergo a well-known problem, zinc dendrite formation, causing internal shorting. Here we show a backside-plating configuration that enables long-term cycling of zinc metal batteries without shorting. We demonstrate 800 stable cycles of nickel–zinc batteries with good power rate (20 mA cm−2, 20 C rate for our anodes). Such a backside-plating method can be applied to not only zinc metal systems but also other metal-based electrodes suffering from internal short circuits.